Iliac Crest Bone Graft for Minimally Invasive Transforaminal Lumbar Interbody Fusion: A Prospective Analysis of Inpatient Pain, Narcotics Consumption, and Costs. Issue 18 (15th September 2018) - Haws, Brittany E.; Khechen, Benjamin; Narain, Ankur S.; Hijji, Fady Y.; Cardinal, Kaitlyn L.; Guntin, Jordan A.; Singh, Kern
Abstract : Study Design: Retrospective Analysis Objective: The aim of this study was to determine whether an association between increased acute pain, postoperative time, and direct hospital costs exists between the use of iliac crest bone grafting (ICBG) and bone morphogenic protein (BMP)-2 following a primary, single-level minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Summary of Background Data: ICBG has been associated with enhanced fusion rates. Concerns have been raised in regards to increased operative time and postoperative pain. The advantages of ICBG compared to other spinal fusion adjuncts have been debated. Methods: Prospective, consecutive analysis of patients undergoing primary, single-level MIS TLIF with ICBG was compared to a historical cohort of consecutive patients that received BMP-2. Operative characteristics were compared between groups using χ 2 analysis or independent t test for categorical and continuous variables, respectively. Postoperative inpatient pain was measured using the Visual Analog Scale, and inpatient narcotics consumption was quantified as oral morphine equivalents. Outcomes were compared between groups using multivariate regression controlling for preoperative characteristics. Results: A total of 98 patients were included in this analysis, 49 in each cohort. No significant differences were noted between cohorts with exception to sex (Females: ICBG, 53.06% vs. BMP-2, 32.65%, P  = 0.041). There was a significant increase in operative time (14.53 minutes, P  = 0.006) and estimated blood loss (16.64 mL, P  = 0.014) in the ICBG cohort. Narcotics consumption was similar between groups on postoperative days 0 and 1. ICBG was associated with decreased total direct costs ($19, 315 vs. $21, 645, P  < 0.001) as compared to BMP-2. Conclusion: Patients undergoing MIS TLIF with ICBG experienced increases in operative time and estimated blood loss that were not clinically significant. Furthermore, iliac crest harvesting did not result in an increase in acute pain or narcotics consumption. Further follow-up is necessary to determine the associated arthrodesis rates and long-term outcomes between each cohort. Level of Evidence: 3